Character Development In William Shakespear’s The Comedy Of Errors Drama - Nisrina Muthi’ah Arsyad; Beby Damayanti Azrin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This journal explores character development in William Shakespeare’s drama “The Comedy of Errors.” Characters play a crucial role in dramas, influencing audience engagement and conveying moral, social, and cultural values. Despite existing research on character analysis, there is a growing need for more specific investigations into drama aspects, particularly character development. Understanding characters enriches the audience’s experience and provides insights into the story’s structure, emotional impact, and moral values. This study aims to analyze characters within the context of character development in the presence of conflict. The research contributes to a deeper understanding of dramatic characters and their roles in conveying moral and cultural values.